Proteomic profiling of muscle fibre type shifting in neuromuscular diseases. (2nd August 2016) - Dowling, Paul; Murphy, Sandra; Ohlendieck, Kay
ABSTRACT: Introduction : Mature skeletal muscles are composed of a complex assembly of slow-twitching, fast-twitching and hybrid fibres. Since muscle fibres exhibit a high degree of cellular plasticity, changed physiological conditions or pathophysiological disturbances have generally a substantial impact on fibre specification. Areas covered : This article reviews the findings from comparative proteomic profiling studies that have focused on neuromuscular diseases and discusses the identified protein changes of fibre type shifting. The reviewed literature on weight loss, obesity, diabetes, cancer cachexia, disuse atrophy, motor neuron disease, myotonia, inflammatory myopathies, myofibrillar myopathies, muscular dystrophies and sarcopenia of old age suggests that proteome-wide alterations occur in the expression of distinct protein families, encompassing especially contractile and regulatory proteins of the acto-myosin apparatus. Expert commentary : The systematic determination of proteome-wide changes in neuromuscular disorders can now be used to design novel diagnostic and therapy-monitoring tools for evaluating fibre transitions in pathological muscles.